Viabilidade e produção de transcritos de virulência por Campylobacter jejuni em leite uht refrigerado - Nalevaiko, Priscila Christen (2015)
Were evaluated the viability and the ability to produce transcripts of ciaB, dnaJ, p19 and sodB genes by C. jejuni experimentally inoculated into UHT milk, after refrigerated storage for 0, 24 and 48 hours. It was used two wild and two reference strains in inoculum of 102 and 104 UFC.mL-1. C. jejuni was recovered in all periods analyzed, but the count of reference strains was only possible at contaminations of 104 UFC.mL-1. The number of recovered cells of the wild strains was higher compared to the reference ones and there was a decrease in the counts during the storage conditioning to the initial inoculum. The ability to transcribe genes showed slight differences between strains, inoculum concentrations and analyzed periods. The transcription of the genes ciaB (invasion), and dnaJ, p19 and sodB (tolerance to environmental stress) was not significant between the strains, but was higher in the 104 inoculum UFC.mL-1. The ability of C. jejuni to remain viable in UHT milk, and the low infectious dose of this species to human infection, indicates that there is danger of acquiring campylobacteriosis by drinking milk, in case of a subsequent recontamination after opening the package. It takes good practices in the handling and storage of this food.